Studies on antidyslipidemic effects of Morinda citrifolia (Noni) fruit, leaves and root extracts - Mandukhail, Saf-ur Rehman (BioMed Central, 2010)
BACKGROUND: The objective of present study was to provide the pharmacological basis for the medicinal use of Morinda citrifolia Linn in dyslipidemia using the aqueous-ethanolic extracts of its fruits (Mc.Cr.F), leaves (Mc.Cr.L) and roots (Mc.Cr.R). RESULTS: Mc.Cr.F, Mc.Cr.L and Mc.Cr.R showed antidyslipidemic effects in both triton (WR-1339) and high fat diet-induced dyslipidemic rat models to variable extents. All three extracts caused reduction in total cholesterol and triglyceride levels in triton-induced dyslipidemia. In high fat diet-induced dyslipidemia all these extracts caused significant reduction in total cholesterol, triglyceride, low density lipoprotein-cholesterol (LDL-C), atherogenic index and TC/HDL ratio. Mc.Cr.R extract also caused increase in high density lipoprotein-cholesterol (HDL-C). The Mc.Cr.L and Mc.Cr.R reduced gain in body weight with a reduction in daily diet consumption but Mc.Cr.F had no effect on body weight and daily diet consumption. CONCLUSIONS: These data indicate that the antidyslipidemic effect of the plant extracts was meditated through the inhibition of biosynthesis, absorption and secretion of lipids. This may be possibly due partly to the presence of antioxidant constituents in this plant. Therefore, this study rationalizes the medicinal use of Morinda citrifolia in dyslipidemia.